Perioperative Safety in the Era of Technological Acceleration (East West Medical College Journal, 2026)
Background: Rapid technological acceleration is transforming perioperative care through the integration of robotic surgery, artificial intelligence (AI), digital monitoring systems, wearable sensors, electronic checklists, and clinical decision-support tools. While these innovations improve precision and efficiency, they also introduce emerging safety challenges that require adaptation of conventional perioperative safety frameworks. Objective: To explore the impact of evolving digital technologies on perioperative safety, identify associated risks and limitations, and highlight strategies for maintaining patient-centred surgical safety in technologically advanced healthcare environments. Discussion: Technological advances in perioperative medicine have enhanced visualization, surgical dexterity, monitoring capabilities, and predictive risk assessment. AI-assisted systems and surgical robotics contribute to improved surgical planning, reduced morbidity, and enhanced procedural precision. However, increasing dependence on automation introduces vulnerabilities including training deficiencies, cognitive overload, cybersecurity threats, interface complexity, and potential system failures. Variability in AI performance across specialties and healthcare settings further emphasizes the need for standardized validation and regulatory oversight. Despite digital transformation, human factors such as communication, teamwork, situational awareness, and clinical judgment remain central to perioperative safety. Continuous clinician oversight, simulation-based training, interdisciplinary collaboration, ethical governance, cybersecurity measures, and ongoing audit systems are essential for safe integration of emerging technologies into surgical practice. Emphasis should also be placed on equitable access and cost-effectiveness to ensure that technological innovations improve safety across both resource-rich and resource-limited settings. Conclusion: Technological innovation is becoming an essential component of modern perioperative care. However, advancement in surgical technology must be accompanied by equally rigorous safety strategies. The future of perioperative medicine depends on achieving effective human–machine synergy while preserving patient-centred care, ethical accountability, and robust safety standards.EWMCJ Vol. 14, No. 2, July 2026: 94-98